Transformational Leadership Management of School Principals in Enhancing the Professional Competence of Primary School Teachers - Adhari Maulana Agung; Okke Rosmaladewi (Journal of Science and Education (JSE), 2025)
This study examines the transformational leadership management of school principals in enhancing the professional competence of primary school teachers. Using a qualitative case study approach, the research was conducted at SDIT Insani and SDIT Andalusia, involving principals, teachers, and managerial staff as key informants. Data were collected through in-depth interviews, direct observations, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings reveal that school principals implement transformational leadership through strategic planning based on teacher needs, the execution of collaborative training programs, structured evaluations, and continuous follow-up actions. These practices reflect the application of the PDCA (Plan–Do–Check–Act) cycle within the framework of educational quality management. Despite limitations in infrastructure and funding, the principals succeeded in fostering a professional and collaborative culture through visionary communication, teacher empowerment, and external partnerships. The study concludes that transformational leadership, when carried out in a planned and adaptive manner, plays a significant role in improving teacher competence and learning quality in primary schools. These findings highlight the importance of strengthening the capacity of school principals as instructional leaders and change agents within school-based educational management.